COVID‐19 and myeloma: what are the implications for now and in the future?. (25th June 2020) - Freeman, Ciara L.; Mikhael, Joseph
Summary: The pandemic has affected every aspect of myeloma care. Immediate focus is minimising risk of contracting coronavirus disease 2019 (COVID‐19) and the sequelae of infection. However, what does the future hold for our patients? What lessons will be taken forward to tackle myeloma in the fiscally constrained future? If we embrace the challenges that will emerge in the post‐pandemic environment, the treatment delivered to patients could be more cost‐effective and better tailored than before. Healthcare delivery post‐COVID‐19 will not return to how it was, and now is the time to invest in novel strategies to deliver the best possible outcomes for patients.